Pharmacokinetics of Isoxsuprine Hydrochloride Administered Orally and Intramuscularly to Female Healthy Volunteers - Marzo, Antonio; Zava, Dario; Coa, Katrin; Bo, Lorenzo Dal; Ismaili, Shefqet; Tavazzi, Simona; Cantoni, Vittorio (Arzneimittelforschung, 2009)
Isoxsuprine (1-(4-hydroxyphenyl)-2-(1-methyl-2-phenoxyethylamino)-1-propanol, CAS 395-28-8) is a peripheral vasodilator that also stimulates betaadrenergic receptors. It causes a direct relaxation of vascular and uterine smooth muscles and produces positive inotropic and chronotropic effects. It is widely used to arrest premature labour and miscarriage. The aim of this trial was to investigate the pharmacokinetics of isoxsuprine hydrochloride administered orally to healthy young female volunteers as an extended-release formulation at the doses of 30, 60 and 90 mg compared to 10 mg by i. m. route. A randomised, crossover, four-period, multisequence, single-dose design was adopted. Plasma and urine concentrations of free and total isoxsuprine were evaluated by tandem mass spectrometry that reached a low quantification limit of 1 ng/ml. From plasma concentrations Cmax, tmax, AUC0–t, AUC0–∞, t1/2 and Vd and from urine concentration CUE0–24h were evaluated by the non-compartmental model.The free drug was present only in plasma after i. m. route, whereas total isoxsuprine, namely the drug after an enzymatic hydrolysis of the conjugate form, was detected in all plasma and urine samples. The distribution volume of the free drug proved to be 2.5 times higher than that of total isoxsuprine, which indicates a good penetration of the free drug into tissue compartments. Oral absorption was evaluated from the p. o./i. m. percentualized ratio of AUC and CUE and proved to be on average around 51%, being linearly correlated with the three doses administered. The oral absorption proved to be sustained as expected from the zero-order kinetics of the drug release from the core of the extended-release formulation. This has justified different values of half-life that was on average 2.2 h after the i. m. route and around 10 h after the three oral doses. After isoxsuprine administration, both oral and i. m. routes, the heart rate increased from baseline during the 9 h monitoring period. This was an expected finding attributable to the stimulating activity of β-adrenergic receptors. The tolerability of isoxsuprine proved to be very good with all the four administrations performed.
Keywords: CAS 395-28-8; Isoxsuprine, intramuscular absorption, oral absorption, pharmacokinetics, urinary excretion; Peripheral vasodilator; Vasosuprina®